The Influence of Transformational Leadership in Improving the Quality of Public Services - Rivaldi, Rivan Diazi; Rohayati, Yeti; Kamil, Indriyati; Indah, Diani (Civiliza Publishing, Indonesia., 2025)
Public service is one of the main indicators of local government performance in realizing effective governance that is responsive to public needs. However, the quality of public services at the sub-district level still faces several problems, such as complicated procedures, delays in service delivery, and low empathy among civil servants. This study aims to analyze the influence of transformational leadership on improving the quality of public services in Cisarua District, Sumedang Regency. This research method uses a quantitative approach with a descriptive-verifiable approach. Data were collected through questionnaires distributed to 55 respondents consisting of leaders, employees, and public service users in Cisarua District. The data were analyzed using validity and reliability tests, as well as simple linear regression to examine the relationship between transformational leadership (X) and public service quality (Y). The results of this study confirm that the implementation of transformational leadership in Cisarua District encourages civil servants to work more professionally, innovatively, and with a strong focus on public satisfaction. Therefore, it is recommended that the local government strengthen leadership training and development programs that emphasize transformational characteristics to continuously improve the quality of public services.